Precordial Catch Syndrome: Unveiling a Benign Yet Noteworthy Cause of Chest Pain in the Young - Koswara, Jonathan; Chen, Jery; Yap, Irianto; Suwanto, Denny (Universitas Airlangga, 2024)
Highlights: 1. An insight on how precordial catch syndrome could be a potential research base for further research because of its rarity. - Background: This syndrome is rarely discussed in the differential diagnosis of chest pain, as it deserves wider recognition. Pediatricians report that PCS accounts for 80% to 90% of chest discomfort in the absence of trauma, primarily in adolescent and young adults. The classic pain history can help identify precordial catch syndrome, often eliminating the need for further testing or referrals. The diagnosis of precordial catch can be challenging due to various inconclusive workups. However, once diagnosed, this condition can be managed conservatively. Objective: This review sought to describe the distinctive features of the syndrome and its management strategy. Method: Descriptive review method was used in this study to provide a comprehensive overview for this study. Results: The pain is sudden in onset, is severe, and is localized above the cardiac apex (fifth intercostal space within the left midclavicular line). General testing is required to exclude various conditions., but several tests like ECG and chest x-ray can be done to rule out other causes of chest pain. Though in pediatric considerations, classic pain history can help identify PCS, often eliminating the need for further testing or referrals. Conclusion: This syndrome deserves wider recognition because it is rarely discussed in the differential diagnosis of precordial pain. Pediatricians report that precordial catch accounts for 80% to 90% of chest pain once any chest trauma is excluded